An Investigation of Knee Injury Prevalence and its Mechanism among Premier League Soccer Referees in Iran - Hamid Mahdavi Mohtasham; Shahnaz Shahrbanian (Biyumikānīk-i varzishī, 2017)
Objective: The aim of the current study was to investigate the knee injury mechanism and its prevalence among the Premier League soccer referees in Iran. Methods: In This cross sectional study a sample of 59 Premier League soccer referees in Iran )age  36.30±4.1 years, height 179±5.8 cm and weight 74.55±6.3 kg( were selected. The information of knee injuries such as injury history, injury mechanism, and effects of knee symptoms on the ability to perform daily activities and recreational activities was obtained through Knee Outcome Survey (KOS). Using the Pearson correlation coefficient, this study examined the relationships between different variables including KOS subscales as well as the current level of self-reported knee joint function and proprioception. Results: The results indicated that 81% of soccer referees experienced knee injury. Meniscus injury accounted for the highest percentage of knee injuries (40%).  In addition, knee injuries of non-dominant leg were more prevalent than those of the dominant leg. Also, the referees were mostly injured during training sessions. The value of KOS was 85±13 for activities of daily living subscale and 90±9 for sports-recreational subscale. Conclusion: The results of this study highlight the importance of including special training in warm-up programs such as interval training, proprioception exercises, strength training (e.g. Nordic hamstring), flexibility training, and muscular endurance training which have been designed to prevent knee injuries. The results help to design and set-up an injury prevention program for the Referees Committee of the Iranian Football Federation.